CRITICAL DISCOURSE ANALYSIS OF THE NEWS OF COVID-19 CORPSE SNATCHING PATIENT IN THE I-NEWS - Rika Astari; Abdul Mukhlis; Muhammad Irfan Faturrahman (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2022)
The diction used in the news of corpse snatching of COVID-19 varies and has caused the public to panic. This study aims to show the structure of the media language used in The News of Corpse Snatching of COVID-19 patients in Pasuruan and the factors that caused the hundreds of people attempting to take the deceased's body forcefully. The primary data are the news of corpse snathing of COVID-19 patients in Pasuruan, uploaded on YouTube and the online news media i-News, and comments from netizens in the comments column. In addition, informant interviews were conducted to show the factors causing Corpse Snatching. Critical discourse analysis (CDA) is used for content analysis by describing three dimensions: text, discursive practice, and social practice. It was concluded that the media language used in the news text of the corpse Snatching in Pasuruan tends to use vocabulary that shows negative rather than positive actions. Moreover, the media emphasizes negative actions more than describing solution actions to become government policy steps. Based on informants and studies of the third dimension, hundreds of people who conducted the Corpse Snatching were caused because people hardly accept COVID-19 protocols since they hold Kejawen Islamic funeral traditions.